Writing for TV and radio a writers' and artists' companion - Teddern, Sue; Warburton, Nick; Angier, Carole 1943-; Cline, Sally (London Bloomsbury Academic, an imprint of Bloomsbury Publishing, 2016)
"This companion offers invaluable insights and solid, practical guidance to those keen to write for TV and radio. Part 1 explores the nature of the media. It looks at the history of writing drama and comedy for radio and TV through a consideration of its key elements and some of the most successful dramas and comedies of past and present. Part 2 includes reflections and tips from award-winning writers of film, television and radio from the UK, the US and Scandinavia. Part 3 offers practical advice on technical aspects of writing for TV and radio including character development, tructure and dialogue. It also gives guidance on how to deal with branches of the broadcasting industry, from agents and actors to producers and script editors"--Provided by publisher.
Part 1. Reflections and experiences. Ten landmark TV dramas and comedies ; Ten landmark radio dramas and comedies ; Horses for courses: TV, radio or both? ; Ten memorable TV and radio characters ; Notes on notes: dealing with feedback ; Having a laugh: writing comedy -- Part 2. Tips and tales, guest contributors -- Part 3. Write on, getting it right, getting it written. That's an idea: tips and techniques to get you started ; Characters: making them memorable ; The building blocks: plot and structure ; A most delicate monster, voice ; The talky bits: writing dialogue ; Hearing their dreams, the nuts and bolts of radio ; The visuals: writing for camera ; INT. desk, day ; Writing is rewriting, or what to do about drafts ; The finishing line ; Reading [+ viewing + listening] list.
"Series editors: Carole Angier and Sally Cline."
Includes bibliographical references (pages 284-288) and index.
Keywords: Television authorship; Radio authorship